An Introduction to Educational Essays for Professional Development of Kindergarten Teachers - Li, Yanli; Hastana (Pacific International Journal, 2022)
The professionalization of early childhood teachers is a new need for teachers in the education reform, an inevitable trend of the times, and an important factor in the quality of kindergarten education and the overall development of young children. Among them, the significance of educational essays to the professional development of teachers and the prosperity of education is indisputable. The author believes that educational essays are the recorder of kindergarten teachers’ daily life, the summarizer of kindergarten teachers’ education and teaching, the practitioner of kindergarten teachers’ scientific research, and the reflector of kindergarten teachers’ teaching practice. Therefore, it is advocated that writing educational essays is an effective learning method for teachers and becomes the basis for teachers to discover themselves, study themselves and improve themselves. The process of educational practice is enhanced by writing educational essays to reflect and summarize and streamline, thus improving teachers’ professionalism and further promoting the progress and prosperity of education.